JBRMR 2017
DOI: 10.24052/jbrmr/v12is01/martfcidtevocf
|View full text |Cite
|
Sign up to set email alerts
|

Market actor's response towards flower colours in determining the economic value of Chrysanthemum flowers

Abstract: Chrysanthemum flowers are a commodity with a chance to be developed. The colour of chrysanthemum flowers determines its economic value, thus becoming a major factor in choosing which types of flowers to be cultivated. This is a survey research. This research was carried out on market actors in Special Region of Daerah Istimewa Yogyakarta (DIY) and Central Java to obtain the preference of chrysanthemum flowers market in supporting Daerah Istimewa Yogyakarta (DIY) as the centre of chrysanthemum seeds and cut flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…In addition to imparting aesthetic appeal to the plant, floral color also plays a crucial role in attracting pollinators for reproduction, offering protection against photo-oxidative damage, and providing resistance to biotic and abiotic stresses [ 44 ]. The visual quality of chrysanthemum is evaluated based on flower color; hence, color is the major determinant of commercial value [ 45 , 46 ]. Central disc florets of chrysanthemum are usually green or yellow in color, and marginal ray florets exhibit diverse colors of red, orange, purple, green, pink, and white [ 47 ].…”
Section: Floral Colormentioning
confidence: 99%
“…In addition to imparting aesthetic appeal to the plant, floral color also plays a crucial role in attracting pollinators for reproduction, offering protection against photo-oxidative damage, and providing resistance to biotic and abiotic stresses [ 44 ]. The visual quality of chrysanthemum is evaluated based on flower color; hence, color is the major determinant of commercial value [ 45 , 46 ]. Central disc florets of chrysanthemum are usually green or yellow in color, and marginal ray florets exhibit diverse colors of red, orange, purple, green, pink, and white [ 47 ].…”
Section: Floral Colormentioning
confidence: 99%
“…A study of consumer preference of Chrysanthemum found that the combination of attributes that is most interested in consumers and chrysanthemum cut flower sellers are quality factors and product specification factors. The quality factors are included flower resistance, stem rigidity, and flower freshness, while the specification factors are included colours, and also other specification factors such as aesthetics, and price [14,15]. Further, other found that pest, disease, and weather are risk factors that become most influenced the Chrysanthemum production [16].…”
Section: Formulation Of Blue Ocean Strategymentioning
confidence: 99%
“…The chrysanthemum business is highly dependent on market demand and prices (Putra et al, 2019). Wijayani et al (2017) found that the largest consumer of cut flowers came from office workers and loyal customers. Events such as weddings, new year, Eid, or certain ceremonies request decoration services from flower material, cut leaves or a series of pot plants (Lintang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%